Identification of Tacca chantrieri (dioscoreaceae) through anatomical and morphological characters - Mohd Noor Nor Nafizah, Wun Shun Jie, Mohamed Fatimah, Daud Norhayati, Alimon Hasimah, (N/A, 2015)
Identification of Tacca chantrieri (dioscoreaceae) through anatomical and morphological characters by Mohd Noor Nor Nafizah, Wun Shun Jie, Mohamed Fatimah, Daud Norhayati, Alimon Hasimah,